Positive alcohol use expectancies moderate the association between anxiety sensitivity and alcohol use across adolescence. (1st June 2018) - Borges, Allison M.; Lejuez, Carl W.; Felton, Julia W.
Highlights: Anxiety sensitivity (AS) and alcohol use expectancies may predict adolescent alcohol use. AS alone did not predict change in alcohol use. AS predicted use for those reporting positive expectancies. Abstract: Anxiety sensitivity (AS), or the fear of anxious symptoms and the belief that these symptoms may have negative physical, social, and cognitive consequences, is one personality trait that emerges in early adolescence and may be linked to alcohol use. However, findings are equivocal as to whether elevated AS during adolescence directly predicts alcohol use. Adolescents do report increases in positive alcohol use expectancies during this developmental period, and these expectancies have been found to be significantly associated with alcohol use. The current study examined whether positive alcohol use expectancies and AS in early adolescence predicted changes in alcohol use throughout adolescence. This aim was examined via secondary data analyses from a longitudinal study examining the development of risk behaviors in adolescents. Results of univariate latent growth curve modeling suggest that AS alone was not a significant predictor of baseline alcohol use or change in use over time after controlling for gender, age, and self-reported anxiety. However, AS in early adolescence was found to be a significant predictor of increases in alcohol use across adolescence for youth who reported greater positive alcohol use expectancies. These results indicate that beliefs regarding the positive effects of alcohol use are an important moderator in the relation between AS and change in alcohol use during adolescence.